Uprooting and planting : essays on Jeremiah for Leslie Allen - Goldingay, John (Library of Hebrew Bible/Old Testament studies ;, 2007)
A group of international scholars examine the location of the prophecies in Jeremiah's life and consider the book's social, ethical, theological, political, and devotional implications. This Festschrift for Leslie C. Allen reflects the ferment in studies of Jeremiah.